Correlation between Oxygen Saturation and Lung Involvement on Chest X-ray in COVID-19 Patients - Ashwini Sankhe; Mridula Muthe; Anagha Joshi; Vikrant Firke; Amith Gaitonde (Asian Journal of Medicine & Health Sciences, 2022)
Background and objectives: The unprecedented outbreak of COVID-19 pneumonia, is putting to test the healthcare facilities of many countries worldwide. In this article we have investigated the correlation between the degree of lung involvement on chest x-ray (CXR) based on a severity score and the oxygen saturation (SpO2) of admitted patients. Methods: In this retrospective observational study, the radiographs of 250 COVID-19 patients taken prior to admission, with confirmed reverse transcriptase polymerase chain reaction (RTPCR) test were analysed using a severity score which was then compared with their blood oxygen saturation levels recorded using pulse oximeter. Also comparison of X-ray severity score was done with age and gender of patients. Results: We found a significant correlation between the CXR score and blood oxygen saturation of patients who were not on oxygen support. However, there was no correlation found between the CXR score and blood oxygen saturation of patients who were on non-invasive ventilation. There was a significant correlation between the CXR score and age of the patient with the severity of the score increasing with the increase in age. There was no correlation found between the CXR score and sex of the patients. Conclusion: We found a significant correlation between SpO2 and CXR findings in patients not on oxygen support, thus indicating that monitoring of patients with SpO2 will prove to be simple and cost effective with the use of radiography limited in patients who are on oxygen support, have worsening disease or for post procedure evaluation.